A potential fault of circuit breaker found using SF6 decomposition products detection. Issue 1 (1st April 2022) - Fu, Lijun; Guan, Yanling; Zhang, Liang; Zhang, Dewen; Wang, Han; Chi, Jingyuan; Wei, Bing
Abstract: A 126kV circuit breaker was found to have latent fault by SF6 decomposition product detection method. It was found that the sulfur hexafluoride gas decomposition products of the circuit breaker contained a large amount of CO gas, a certain amount of SO2 and H2 S, and a small amount of HF gas. The characteristic components and their contents of the decomposition products were analyzed, it is preliminarily concluded that there is insulation material fault in the circuit breaker, and the potential fault is further confirmed by the disassembly inspection that the MoS2 lithium base grease is overcoated at the metal tie rod joint.